Anterior deflected urinary stream in female children: description of a unique clinical entity and surgical management - Swallow, Matthew S.; Sharadin, Cynthia A.; Schaeffer, Anthony J.; Jacobson, Deborah L.; Lau, Glen A. (Frontiers in Pediatrics, 2024)
Objectives To investigate the clinical presentation and outcomes for a series of female pediatric patients with severe anterior deflection of the urinary stream (ADUS) who were managed via urethromeatoplasty. Methods This single institution retrospective cohort study used the institutional billing database to identify female patients ≤18 years who received a urethromeatoplasty (CPT 53450) from 2007 to 2022. Patients were included if a substantial anterior deflection of their urinary stream was the primary indication for surgery. Patients were excluded if they were >18 years of age, had a history of prior genital trauma, or underwent surgery for an indication other than a deflected urinary stream. Results Twenty female patients underwent urethromeatoplasty between 2007 and 2022, with a median age of 3 years old. All patients presented with difficulty aiming the urinary stream during toilet training and demonstrated a web of tissue along the posterior aspect of the urethral orifice. 19/20 patients noted immediate response (i.e., normal, non-deflected urinary stream) after the urethromeatoplasty with no further urinary complaints. There were no post-operative complications within a 90-day period. Conclusions ADUS is a clinical entity characterized by a web of deflecting tissue at the female posterior urethral meatus that causes severe urinary deflection without other urologic symptoms. This is not well-described in the literature. Surgical correction via urethromeatoplasty is safe and effective.